2017
DOI: 10.1007/s00261-017-1179-3
|View full text |Cite|
|
Sign up to set email alerts
|

Fertility-sparing for young patients with gynecologic cancer: How MRI can guide patient selection prior to conservative management

Abstract: Historically, cancer treatment has emphasized measures for the “cure” regardless of the long-term consequences. Advances in cancer detection and treatment have resulted in improved outcomes bringing to the fore various quality of life considerations including future fertility. For many young cancer patients, fertility preservation is now an integral component of clinical decision-making and treatment design. Optimal fertility-sparing options for young patients with gynecologic cancer are influenced by patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 145 publications
(266 reference statements)
0
21
0
1
Order By: Relevance
“…In our series, cervical shape modifications were observed and correctly diagnosed as post-conization modifications, being aware of CKC location. Ideal cervical length, measured on sagittal T2WI from the internal to external os, should be > 2.5 cm [11]. In case of extra conization, this information is important to avoid obstetrical complications, such as cervical incompetence and future preterm delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our series, cervical shape modifications were observed and correctly diagnosed as post-conization modifications, being aware of CKC location. Ideal cervical length, measured on sagittal T2WI from the internal to external os, should be > 2.5 cm [11]. In case of extra conization, this information is important to avoid obstetrical complications, such as cervical incompetence and future preterm delivery.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is reported to be very accurate in selecting patients eligible for FSS [10,11], in tumor size evaluation and deep stromal invasion assessment [12]. In the evaluation of parametrial invasion, the specificity and negative predictive value of MRI were 97% and 100%, respectively [13].…”
Section: Introductionmentioning
confidence: 99%
“…The role of pelvic MRI to determine the depth of invasion has been described in detail. [27] The negative predictive value of MRI to exclude deep myometrial invasion is higher than 95%.…”
Section: Diagnostic Imagingmentioning
confidence: 98%
“…7 17 18 Among the literature on endometrial cancer and fertility-sparing, we selected three on MRI and one on MRI and ultrasound evaluation. In particular, we found three retrospective studies [28][29][30] on MRI and endometrial cancer and one narrative review on MRI and ultrasound; 31 and three articles (two descriptive studies 6 7 and one narrative review 5 ) reported fertility-sparing and gynecological cancer including data on MRI parameters for fertility preservation in endometrial cancer patients (Table 1). Myometrial and cervical stromal invasion: absence of myometrial and cervical invasion is required to consider fertility-sparing treatment.…”
Section: Endometrial Cancermentioning
confidence: 99%
“…3 Defining which patients are eligible for fertility preservation significantly relies on accurate cancer staging. In this context, ultrasound evaluation 4 and MRI [5][6][7] play an important role in the preoperative assessment of gynecological cancers.…”
Section: Introductionmentioning
confidence: 99%